Pemanfaatan Tepung Mocaf Dalam Pembuatan Sponge Cake - Jovita Nuriza; Niken Purwidiani; Ila Huda Puspita Dewi; Mauren Gita Miranti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Sponge cake is a sweet cake snack that is often consumed throughout the world and is made from flour, sugar, eggs, emulsifier, and others. In this research, sponge cake was innovated by using mocaf flour as a substitute for wheat flour. This research aims to determine: 1) the potential of mocaf flour as a substitute for wheat flour in making sponge cake through organoleptic tests; 2) the nutritional content contained in sponge cake made from mocaf flour; and 3) selling price for mocaf flour sponge cake. The research method used in this research was an experimental method which was tested on 30 panelists and then analyzed using a single ANOVA with the SPSS program, testing the nutritional content of mocaf flour sponge cake using chemical tests in the laboratory and to determine the selling price it was analyzed using conventional methods. The results of this research show that: 1) the ratio of mocaf flour and wheat flour 80:20 has a higher average value than the other comparison values, then there is a significant change in color and texture, and there is no significant change in taste, odor, pores, and scale; 2) the nutritional content of the mocaf flour sponge cake based on laboratory tests shows that per 100 grams it has a total of 234.80 kcal calories, 46.15% carbohydrates, 8.11% protein content, 2.05% fat content, 1.62% fiber %, water content 39.88%, and ash content 1.67%; and 3) the selling price for mocaf flour sponge cake products is IDR 4,914.76/50gram.